Advances in Functional Micro-/Nanoimaging Probes (Engineering Materials,, 2018)
Given the rapid emergence of transdisciplinary research and applications in materials, chemical probes and translational medicine in recent years, scientists in these areas are expected to keep up to date on the latest technologies and advances to promote comprehensive innovations. Addressing this need, the book presents recently introduced features, emerging techniques, and new strategies, complemented by detailed illustrations. Covering the status quo and offering an outlook on the future, it benefits all readers with an interest in functional materials, especially micro/nano imaging materials for biomedical imaging applications, providing them with both vital updates and inspiration for their own research.